THE USE OF LANGUAGE OF NEGOTIATION BETWEEN SELLERS AND BUYERS AT KARISA TRADITIONAL MARKET JENEPONTO REGENCY - Nur Fadillah; Abdul Wahid; Andi Hajar (International Journal of Business English and Communication, 2023)
This study analyzed the use of language of negotiation between sellers and buyers at Karisa traditional market in Jeneponto Regency using a qualitative approach. Data was collected through observation, recording, and interviews, and analyzed using discourse analysis. The study found that both sellers and buyers use various linguistic strategies, including bargaining, flattery, and persuasive language, to achieve a successful negotiation outcome. Additionally, the use of local languages, such as Bugis, Makassar, and Jeneponto, is common in the negotiation process to establish a sense of familiarity and trust. The study suggests that the use of local languages should be considered in the negotiation process, particularly in traditional markets. Based on these results, The study did not identify a single "best" way to use the language of negotiation, as the use of different linguistic strategies depended on the negotiation context and individual preferences. However, the study did find that some linguistic strategies were more effective than others in achieving a successful negotiation outcome. For example, both sellers and buyers found that bargaining and the use of persuasive language were effective in persuading the other party to agree to a favorable price or deal. Furthermore, the use of local languages was found to be an effective way to establish a sense of trust and rapport between the sellers and buyers. These findings highlight the importance of understanding the negotiation context and the preferences of the other party to use the language of negotiation effectively.